Hubungan antara Dukungan Sosial dengan Resiliensi Penyintas COVID-19 di Wilayah Kerja Puskesmas Kaliwates Jember: The Relationship Between Social Support and Resilience Among COVID-19 Survivors in the Working Area of Kaliwates Health Center, Jember - Aditya Kusuma Wardana; Erti Ikhtiarini Dewi; Yeni Fitria (NERS Jurnal Keperawatan, 2023)
Survivors are vulnerable to mental health problems. Mental health problems in COVID-19 survivors that can occur are anxiety, fear, disappointment, and sadness. Social support can be one of the efforts that can be made. This research aims to analyze the correlation of social support with the resilience of COVID-19 survivors in the working area of the Kaliwates Jember Health Center. This research uses a quantitative method with an analytical observational design with a cross-sectional approach. The number of samples in this research was 176 COVID-19 survivors and were selected using the simple random sampling technique. Data were obtained using the Multidimensional Scale of Perceived Social Support (MSPSS) and Connor-Davidson Resilience Scale (CD-RISC-25) questionnaires. The results showed that the respondents had high social support (94.3%) and moderate resilience (64.2%). Data analysis using the Spearman’s-rank correlation test showed a moderately positive relationship between social support and resilience in COVID-19 survivors in the work area of the Kaliwates Jember Health Center (p = 0.000 and r = 0.574). The higher the social support, the higher the resilience of COVID-19 survivors. Providing holistic nursing care with social support is essential to improve or maintain good resilience in COVID-19 survivors.